Induksi Superovulasi dengan Kombinasi CIDR, Hormon FSH dan hCG pada Induk Sapi Potong - E M Kaiin; B Tappa (Media Peternakan, 2006)
The aim of this study was to evaluate the effect of superovulation treatment using combination of CIDR, FSH and hCG in beef cattle as donor embryos using MOET programme. All animals had been palpated to evaluated the ovary status and normal cows were used as donor and synchronized with CIDR (Eazy BreedTM). At day 10 of oestrus cycle, cows were divided into two groups, first group: cows were injected intramuscularly with FSH (Antrin) 40 IU per cow with decreasing doses (for 4 days) and second group cows were treated the same way but at day 5 after FSH injection, they were injected intramuscularly with 1,500 IU hCG (Chorulon). Embryo collection was done at day 7 after Artificial Insemination (AI). Average number of corpora lutea (CL) in animals that superovulated with CIDR, FSH and hCG was significantly higher (P < 0.05) compared to animals treated with CIDR and FSH only (5.52). Average number of embryo collection and number of transferable embryos were also higher in group treated with hCG (6.00 vs 5.44) compared with those treated without hCG (4.33 vs 3.17). The conclusion is hCG superovulation injection with CIDR and FSH can increase the respon of superovulation. Key words : superovulation, CIDR, FSH, hCG, beef cattle